2016
DOI: 10.3399/bjgp16x687985
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients with non-metastatic colorectal cancer in primary care: a case-control study

Abstract: ConclusionBleeding combined with either diarrhoea, constipation, change in bowel habit, or abdominal pain are the most powerful predictors of nonmetastatic colorectal cancer and should result in prompt referral for colorectal investigation. In order to increase survival rates for people with colorectal cancer, the most important factor is to be able to identify patients with a potentially curable disease. Sweden has high survival rates in colorectal cancer, despite not having a national screening programme. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…The rationale for standardized care pathways has been to improve identification of patients with a wellfounded suspicion of cancer. Our results confirm results from previous studies [13] that the most frequent symptom in patients subsequently diagnosed with rectal cancer was rectal bleeding. This symptom occurred in three-quarters of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…The rationale for standardized care pathways has been to improve identification of patients with a wellfounded suspicion of cancer. Our results confirm results from previous studies [13] that the most frequent symptom in patients subsequently diagnosed with rectal cancer was rectal bleeding. This symptom occurred in three-quarters of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study suggested that some symptoms, such as loss of appetite, weight loss, fatigue, and fever/flu presentations, were associated with a high‐lung cancer risk . Furthermore, some of the presented symptoms, such as jaundice, are likely to represent advanced colorectal cancer . A study based on the general population indicated that the incidences of these symptoms were not associated with disease stage .…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, some of the presented symptoms, such as jaundice, are likely to represent advanced colorectal cancer. 24 A study based on the general population indicated that the incidences of these symptoms were not associated with disease stage. 25 However, few studies have reported the relationship between the symptoms and physical signs of lung cancer and the stage of cancer, particularly for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…15 Since then, English and Swedish case-control studies have reported that weight loss is associated with acute and chronic leukaemia and non-metastatic colorectal cancer. 35,36 For some cancer sites there have been no studies on the association with unexpected weight loss in primary care. Our analysis is the first to focus on the association between unexpected weight loss and cancer across all sites.…”
Section: Findings In Contextmentioning
confidence: 99%